ANALISIS PENGARUH TATA KELOLA PERUSAHAAN DAN KARAKTERISTIK DIREKTUR UTAMA TERHADAP TINDAKAN PAJAK AGRESIF DI INDONESIA - Robi Asroni; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2019)
This research was aimed to analyze the effect of corporate governance, executive compensation, and CEO characteristics on the level of tax aggressiveness. Tax aggressiveness measured by the effective tax rate (ETR). Corporate governance proxied by the amount of the board of directors and the percentage of independent commissioners. CEO characteristics are proxied by the age and tenure of CEO. Firm size, firm performance, and capital intensity are used as control variables.The population of this research was all financial sectors firm listed on the Indonesia Stock Exchange (IDX) during 2014-2016. The sample was selected using a purposive sampling method and obtained 191 companies. This research uses quantitative methods using multiple linear regression analysis.The results showed that the size of the amount of board directors and the percentage of independent commissioners have a significant positive effect on tax aggressiveness. The executive compensation and the CEO age have a negative effect on tax aggressiveness. Meanwhile, the term of CEO tenure has a positive but not significant effect on tax aggressiveness.